Cu doped NiO thin film photocathodes for enhanced PEC performance - Sahoo, Pooja; Sharma, Akash; Padhan, Subash; Thangavel, R. (Superlattices and microstructures, 2021)
The present report describes the fabrication of undoped NiO and Cu doped NiO based photocathodes synthesized by sol gel spin coating technique. Mott-Schottky, LSV and EIS measurements have been carried out to investigate the PEC properties of these photocathodes. 3% Cu doped NiO film exhibits the highest PEC performance among all photocathodes. The p-type semiconducting nature of all thin film samples has been confirmed from the M-S plots. Also, the values of carrier density have been tuned from 1.18 × 1020 to 1.36 × 1020 cm−3 for undoped NiO and 3% Cu doped NiO thin films. VB CB levels of the as-prepared photocathodes have been calculated from absorption spectra. 3Cu:NiO exhibits a significantly higher photocurrent density of −6.97 mA/cm2 at −1.5 V vs. Ag/AgCl in 0.1M NaOH solution under UV illumination. The superior PEC performance is due to efficient charge transport and reduced recombination rate of the photogenerated electron-hole pairs. These findings demonstrate the potential of Cu doped NiO photocathodes in water splitting applications. [Display omitted] •NiO and Cu doped NiO thi films fabrication was carried out via sol-gel, spin coating technique.•3Cu:NiO exhibited the highest photocurrent denisty of -6.97 mA/cm2 at -1.5V vs Ag/AgCl under UV light.•Carrier density of 1.36 x 1020 cm-3 was estimated for 3Cu:NiO from Mott-Schottky Analysis.